Influence of dam geometry on the breaching process of landslide dams. Issue 5 (October 2021) - Shi, Z M; Zhang, G D; Peng, M; Ma, C Y
Abstract: The breaching process of landslide dams is influenced by many factors. In this study, several laboratory experiments on the overtopping of landslide dam were conducted to investigate the specific effects of dam geometry on the breaching process of landslide dams. According to the test results, geometric parameters of the dam, including dam height, crest width, and downstream slope, had considerable effects on the breaching process. The breaching process was divided into three stages: (1) breach initiation stage, (2) breach development stage, and (3) attenuating and reequilibrium stage. Dam height reflected the volume of impoundment and affected the breach development stage. With the increase of the dam height, the peak discharge increased, and its time of arrival was delayed. The dam crest width affected the breach initiation stage. The peak discharge increased significantly, and its arrival time was shortened by the decrease in the dam crest width. Downstream slope reflected the dam stability and affected the breach initiation and breach development stages. With the decrease of the downstream slope, the peak discharge decreased, and its time of arrival was delayed considerably.